Ketahanan Keluarga dan Implementasi Fikih Keluarga pada Keluarga Muslim Milenial di Gresik, Indonesia: Ketahanan Keluarga dan Implementasi Fikih Keluarga pada Keluarga Muslim Milenial di Gresik, Indonesia - Fathoni, Achmad (Institut Agama Islam Negeri (IAIN) Pontianak, 2021)
Family resilience is a national issue in improving the population’s quality during the rapid flow of information technology development. Ideally, the development of information technology makes life easier, especially for millennial Muslim families. The use of social media can cause problems in the family. This article aims to determine the resilience of millennial Muslim families in economic, social, and psychological aspects and implement family jurisprudence. This study is qualitative research with two data collection techniques: an online survey using a google form and interviews with three married couples in Gresik, Indonesia. The results showed that the resilience of millennial Muslim families was classified as good in terms of economic resilience, social resilience, and psychological resilience. Aspects of economic resilience are measured by employment status, income, and residence status. The aspect of social resilience is assessed from the pattern of communication and participation in social activities. Aspects of psychological resilience are seen from problem solving and efforts to maintain harmony in the family. These three aspects, consciously or not, have shown the implementation of family jurisprudence in millennial Muslim families in Gresik. The author argues that the better the implementation of family fiqh in a millennial Muslim family, the better the family resilience will be.